Method for forming glassy coating film

JP2025027545APending Publication Date: 2025-02-28AQUA SCI CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023132363
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0014】 本件出願に係る発明によれば、金属材又は樹脂材からなる被コーティング対象物の表面を紫外線や砂塵等の様々な外的要因から保護すると共に、高い撥水性や耐食性を付与するための、当該被コーティング対象物に対するコーティング膜の形成方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027545000001
    Figure 2025027545000001
Patent Text Reader

Abstract

To provide a method for forming a glassy coating film that protects a surface of an object to be coated from external factors such as ultraviolet ray and sand dust, and also forms a coating film for applying high water repellency and corrosion resistance, on the object to be coated.SOLUTION: A method for forming a glassy coating film adopts a method for forming a glassy coating film including the following steps 1-3: a step 1 of defatting and washing a surface of an object to be coated and then drying the surface; a step 2 of applying, to the dried surface of the object to be coated, coating liquid which includes predetermined quantities of active ingredients composed of methyl trimethoxy silane or methyl triethoxysilane, vinyl trimethoxy silane or vinyl triethoxysilane and titanium tetra butoxide; and a step 3 of applying reaction liquid including predetermined quantities of water to the object to be coated applied with the coating liquid, so as to form a glassy coating film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for forming a glassy coating film. In particular, the present invention relates to a technology for imparting water repellency and weather resistance to an object to be coated by providing a glassy coating film on the surface of the object to be coated, the object being made of a metal material or a resin material. [Background technology]

[0002] Metal materials such as aluminum or aluminum alloys, copper or copper alloys, and resin materials such as polycarbonate resin (PC resin) and polymethyl methacrylate resin (PMMA resin) are highly durable and have good processability, and therefore are used in various fields such as daily necessities, automobile bodies and parts, and aircraft bodies and parts. Here, products used outdoors, such as automobile bodies and parts and aircraft bodies and parts, also need to have excellent weather resistance. For this reason, technologies have been studied that provide a coating film on the surface of metal materials and resin materials used in these products to protect the surface from external factors such as ultraviolet rays and dust, and to impart high water repellency and corrosion resistance.

[0003] Patent Document 1 discloses a coating film forming method for forming a coating film on the surface of an object having a hydrophobic surface made of metal, plastic, glass, etc., by applying a coating liquid in which fine particles having hydrophobic surfaces are dispersed in an organic solvent containing a predetermined amount of a hydrophobic solvent.

[0004] Furthermore, Patent Document 2 discloses a "corrosion-resistant water-based coating composition for use on metal materials such as aluminum and inorganic materials, which contains a coating resin having a specified amount of silicon in the solid content and a film-forming aid." [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-155727 A [Patent Document 2] JP 2007-169353 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the coating film forming method of Patent Document 1 requires a pretreatment to make the surface of the target object (coated object) such as metal hydrophobic, which makes the production time-consuming and increases the production cost. In addition, the corrosion-resistant water-based paint composition of Patent Document 2 is mainly composed of paint resin, so that the hardness of the obtained coating film may not satisfy the required specifications depending on the product in which it is used.

[0007] For this reason, there is a continuing demand among those skilled in the art for a method of forming a coating film on an object to be coated, which protects the surface of the object to be coated, made of a metal or resin material, from various external factors such as ultraviolet rays and dust, and also imparts high water repellency and corrosion resistance to the object.

[0008] Therefore, as a result of intensive research, the inventors of the present invention have come up with the following invention, which solves the above-mentioned problems. [Means for solving the problem]

[0009] The invention according to the present application is a method for forming a glassy coating film on an object to be coated in order to impart water repellency to the object, and is characterized by including the following steps 1 to 3.

[0010] Step 1: The object to be coated, which is made of metal or resin, is degreased, washed, and then dried. Step 2: Absolute humidity 18.4g / m 3Under the following conditions, a coating liquid containing 80% by mass or more of active ingredients consisting of 15% by mass to 65% by mass of vinyltrimethoxysilane or vinyltriethoxysilane, 0.3% by mass to 2.7% by mass of titanium tetrabutoxide, and the remainder being methyltrimethoxysilane or methyltriethoxysilane, is applied to the surface of the coated object after drying. Step 3: Absolute humidity 18.4g / m 3 Under the following conditions, a reaction liquid containing 65% or more by mass of water is applied to the object to be coated to which the coating liquid has been applied, to form a glassy coating film on the surface of the object to be coated.

[0011] In the invention according to the present application, the temperatures of the coating liquid in step 2 and the reaction liquid in step 3 are preferably 5°C to 55°C.

[0012] When the coating in steps 2 and 3 of the present invention is carried out by spraying, the particle size of the droplets when the coating liquid and the reaction liquid are sprayed is preferably 50 μm or less.

[0013] When the coating in steps 2 and 3 of the invention of the present application is carried out by a spraying method, it is preferable that the flow velocity of droplets when the coating liquid is sprayed in step 2 is 55 m / sec to 145 m / sec, and the flow velocity of droplets when the reaction liquid is sprayed in step 3 is 1 m / sec to 30 m / sec. Effect of the Invention

[0014] According to the invention of the present application, a method for forming a coating film on an object to be coated, which is made of a metal or resin material, can be provided to protect the surface of the object to be coated from various external factors such as ultraviolet rays and dust, and to impart high water repellency and corrosion resistance to the object. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The invention according to the present application is a method for forming a glassy coating film on an object to be coated in order to impart water repellency to the object, and is characterized by including the following steps 1 to 3. Each step will be described below.

[0016] Step 1: The object to be coated, which is made of metal or resin, is degreased, washed, and then dried.

[0017] The object to be coated used in this step 1 is a metal material or a resin material. There is no particular limit to the type of metal material, and examples of the metal material include pure aluminum such as A1050, aluminum alloys such as A5052 and A2017, copper, copper alloys, and the like. There is no particular limit to the type of resin material, as long as there is no risk of the surface being eroded when the coating liquid used in the next step is applied to the surface, and examples of the resin material include polycarbonate resin (PC resin), polymethyl methacrylate resin (PMMA resin), and the like. There is also no particular limit to the method of degreasing, washing, and drying the object to be coated, and conventionally known methods may be used. Specifically, for example, the surface of the object to be coated may be degreased and washed with a commercially available neutral detergent containing a surfactant, followed by washing with water, and the object to be coated may be sufficiently dried using an air blow gun or the like.

[0018] Step 2: Absolute humidity 18.4g / m 3 Under the following conditions, a coating liquid containing 80% by mass or more of active ingredients consisting of 15% by mass to 65% by mass of vinyltrimethoxysilane or vinyltriethoxysilane, 0.3% by mass to 2.7% by mass of titanium tetrabutoxide, and the remainder being methyltrimethoxysilane or methyltriethoxysilane, is applied to the surface of the coated object after drying.

[0019] The coating liquid used in step 2 contains 80% by mass or more of active ingredients consisting of methyltrimethoxysilane or methyltriethoxysilane, vinyltrimethoxysilane or vinyltriethoxysilane, and titanium tetrabutoxide. Among the active ingredients, methyltrimethoxysilane or methyltriethoxysilane is the main component of the coating liquid, and when a reaction liquid mainly composed of water is applied in the next step, it becomes a glassy coating film by hydrolysis. Similarly, vinyltrimethoxysilane or vinyltriethoxysilane becomes a part of the glassy coating film by hydrolysis when a reaction liquid mainly composed of water is applied in the next step, but in the invention of the present application, these compounds are used as auxiliary agents to obtain a water-repellent glassy coating film. Titanium tetrabutoxide is a catalyst when the main component and auxiliary agents come into contact with water in the reaction liquid and cause a hydrolysis reaction, and is intended to enable the rapid formation of a glassy coating film on the surface of the object to be coated at around room temperature.

[0020] In addition to the above-mentioned effective ingredients, the coating liquid used in step 2 preferably contains alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol, dyes or pigments such as rhodamine B, indigo, and phthalocyanine blue, and fillers such as boron nitride and anhydrous magnesium carbonate. If the coating liquid contains alcohols, the viscosity is reduced, making it easier to apply the coating to the object to be coated. If the coating liquid contains dyes or pigments, a glassy coating film with various appearance colors can be formed. If the coating liquid contains fillers such as boron nitride and anhydrous magnesium carbonate, the glassy coating film can be used as a thermally conductive insulating film.

[0021] Here, the preferred content of the active ingredient in the coating liquid is 80% by mass or more. If the content of the active ingredient is less than 80% by mass, a separate step such as leaving the object to be coated in a thermostatic chamber set at about 65°C to 80°C after applying a reaction liquid mainly composed of water in the next step is required, and the hardness of the glassy coating film tends to decrease, which is not preferred. On the other hand, there is no particular limit to the upper limit of the preferred content of the active ingredient in the coating liquid, and it is also preferred to use a coating liquid consisting only of the above-mentioned active ingredient, since this reduces production costs. The values ​​regarding the content of the active ingredient in the coating liquid are stated excluding inevitable impurities.

[0022] In addition, the preferred content of each component constituting the active ingredient in the coating liquid used in step 2 is 15% to 65% by mass of vinyltrimethoxysilane or vinyltriethoxysilane, 0.3% to 2.7% by mass of titanium tetrabutoxide, and the remainder is methyltrimethoxysilane or methyltriethoxysilane, when the total amount of the active ingredients is taken as 100% by mass. Note that these values ​​regarding the content of each component in the coating liquid are stated excluding inevitable impurities. Here, if the content of vinyltrimethoxysilane or vinyltriethoxysilane is less than 15% by mass, it is not preferable because it tends not to obtain a glassy coating film having water repellency (i.e., a glassy coating film in which the contact angle between the surface and the water droplet is 90 degrees or more when water is dropped on the surface). On the other hand, even if the content of vinyltrimethoxysilane or vinyltriethoxysilane exceeds 65% by mass, it is not preferable because it tends not to obtain a glassy coating film having water repellency. Also, if the content of titanium tetrabutoxide is less than 0.3% by mass, the catalytic action is not fully expressed, and the hydrolysis rate of the components (the main agent and auxiliary agent described above) contained in the coating liquid when the reaction liquid containing water as the main component is applied in the next step is extremely slow, and in order to maintain the work efficiency, a separate step such as leaving the coated object in a thermostatic chamber set at about 65°C to 80°C after applying the reaction liquid in the next step is likely to be required, which is not preferable. On the other hand, even if the content of titanium tetrabutoxide exceeds 2.7% by mass, the hydrolysis rate of the components contained in the coating liquid is extremely accelerated, and a transparent glass-like coating film with good appearance tends not to be obtained, which is also not preferable.

[0023] The process 2 and the next process 3 are carried out at an absolute humidity of 18.4 g / m 3 This must be done under the following conditions: absolute humidity 18.4g / m 3 corresponds to the amount of moisture in the air at a temperature of 25°C, a relative humidity of 80%, and a pressure of 1 atmosphere. Here, the work in step 2 and the next step 3 are carried out at an absolute humidity of 18.4 g / m 3If the coating liquid is applied to the surface of the object to be coated in an environment exceeding this absolute humidity, the components (main agent and auxiliary agent) contained in the coating liquid will react with moisture in the air, and will solidify in part or in whole before the reaction liquid, the main component of which is water, is applied in the next step, which tends to make it difficult to reproducibly form the desired glassy coating film. On the other hand, there is no particular limit to the lower limit of this absolute humidity, but the work in this step 2 and the next step 3 should be carried out at an absolute humidity of 3.8 g / m 3 It is preferable to carry out the test under the above-mentioned conditions. 3 corresponds to the amount of moisture in the air at a temperature of 15°C, relative humidity of 30%, and pressure of 1 atmosphere. 3 If the process is carried out in an environment less than this temperature, it becomes somewhat difficult to control the reaction rate between the components (main agent and auxiliary agent) contained in the coating liquid applied to the surface of the object to be coated and the water contained in the reaction liquid to be applied in the next process, and it tends not to be possible to reproducibly form the desired glassy coating film.

[0024] Step 3: Absolute humidity 18.4g / m 3 Under the following conditions, a reaction liquid containing 65% or more by mass of water is applied to an object to be coated to which a coating liquid has been applied, thereby forming a glassy coating film on the surface of the object to be coated.

[0025] The main component of the reaction liquid used in step 3 is water. There is no particular restriction on the type of water, and pure water (distilled water, ion-exchanged water, etc.) or tap water may be used. By applying a reaction liquid mainly composed of water in step 3 on the surface of the liquid film composed of the coating liquid applied in step 2, the components contained in the coating liquid come into contact with the water in the reaction liquid and undergo a hydrolysis reaction to form a glassy coating film. The reason why the coating liquid and water are separated and applied to the object to be coated as two chemical liquids, rather than preparing one chemical liquid by adding water as a component to the coating liquid and applying this to the object to be coated, is that if water is added to the above-mentioned coating liquid, it will solidify within a few minutes, and the pot life will be extremely short. On the other hand, if a method of applying a reaction liquid mainly composed of water in step 3 on the surface of the liquid film composed of the coating liquid applied in step 2 as in the invention of the present application, the coating liquid will not solidify in the container and can be stored for a relatively long period of time at around room temperature. Incidentally, the above-mentioned step 2 and this step 3 may be carried out successively as coating operations, and it is not necessary to leave the object to be coated with the coating liquid applied thereto for a predetermined period of time.

[0026] In addition to the water, the reaction liquid used in step 3 preferably contains alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, etc. If the coating liquid contains alcohols, the hydrolysis reaction rate is slightly slower, and a transparent glass-like coating film with good appearance can be obtained with good reproducibility.

[0027] The preferred water content in the reaction liquid is 65% by mass or more. If the water content is less than 65% by mass, a separate step such as leaving the object to be coated in a thermostatic chamber set at about 65°C to 80°C after applying the reaction liquid mainly composed of water in step 3 is required, or the amount of water is insufficient, causing the hydrolysis reaction to not proceed sufficiently, and the surface of the glassy coating film to become sticky, which is undesirable. On the other hand, there is no particular limit to the upper limit of the preferred water content in the reaction liquid, and it is also preferable to use a reaction liquid consisting of only water, since this reduces production costs.

[0028] In the invention according to the present application, it is preferable to adjust the amounts of the coating liquid and the reaction liquid to be applied onto the surface of the object to be coated so that a glassy coating film having a thickness of 0.5 μm to 2.5 μm is formed on the surface of the object to be coated by performing the above-mentioned step 2 and step 3 in this order once (i.e., performing one application cycle). Here, if the thickness of the glassy coating film obtained by one application cycle is less than 0.5 μm, the glassy coating film tends to be relatively easily damaged, and the function of protecting the surface of the object to be coated tends to be insufficient, which is not preferable. On the other hand, if the thickness of the glassy coating film obtained by one application cycle exceeds 2.5 μm, it is not preferable because the glassy coating film tends to be a lackluster glassy coating film that is partially or entirely cloudy. The amounts of coating liquid and reaction liquid required to form a glassy coating film having a thickness within this numerical range may be appropriately determined depending on the surface area of ​​the object to be coated when the application in the above-mentioned step 2 and step 3 is performed by a potting method, the pulling speed of the object to be coated immersed in the coating liquid when the application is performed by a dip coating method, and the flow rate of the droplets and the distance between the surface of the object to be coated and the tip of the spray nozzle of the sprayer when the application is performed by a spraying method.

[0029] However, regarding the ratio of the amount of the coating liquid applied on the surface of the object to be coated in the above-mentioned step 2 to the amount of the reaction liquid applied on the surface of the liquid film made of the coating liquid in this step 3, when the total mass of the active ingredients (methyltrimethoxysilane or methyltriethoxysilane, vinyltrimethoxysilane or vinyltriethoxysilane, and titanium tetrabutoxide) contained in the coating liquid is taken as 1, the mass of water contained in the reaction liquid is preferably 1 / 3 to 1. When the coating liquid according to the present application is applied to the object to be coated so as to wet and spread over the entire surface on which a glassy coating film is to be formed, if the mass of water relative to the total mass of the active ingredients on the surface of the object to be coated is less than 1 / 3, the hydrolysis reaction of the active ingredients does not proceed sufficiently, and the surface of the glassy coating film tends to become sticky, which is not preferable. On the other hand, if the mass of water relative to the total mass of the active ingredients on the surface of the object to be coated exceeds 1, it takes time and effort to dry and remove the excess water, which tends to increase the production cost, which is not preferable.

[0030] Here, the temperature of the coating liquid in the above-mentioned step 2 and the reaction liquid in the present step 3 is preferably 5°C to 55°C. If the temperature of the coating liquid in the step 2 is less than 5°C, the viscosity of the coating liquid becomes slightly high, and when the coating liquid according to the present application is applied to the object to be coated, frost tends to adhere to the surface of the liquid film made of the coating liquid, and a transparent glassy coating film with good appearance tends not to be obtained, which is not preferable. There is no problem with the temperature of the reaction liquid in the step 3 as long as it is not below the freezing temperature, but even if the temperature of the reaction liquid is less than 5°C, the film quality of the glassy coating film does not change significantly, and it tends to simply increase the production cost required for cooling, which is not preferable. On the other hand, if the temperature of the coating liquid in the above-mentioned step 2 and the reaction liquid in the present step 3 exceeds 55°C, the rate of hydrolysis reaction that occurs when the components contained in the coating liquid come into contact with the water in the reaction liquid becomes too high, and part or all of the glassy coating film tends to become cloudy, which is not preferable. In addition, it is more preferable that the temperature of the coating liquid in the above-mentioned step 2 and the reaction liquid in the present step 3 is 15°C to 30°C. When the temperatures of the coating liquid in the above-mentioned step 2 and the reaction liquid in the present step 3 are within this numerical range, a glassy coating film that is more stably transparent and has a good appearance tends to be obtained, and the production costs required for cooling or heating the coating liquid and the reaction liquid can be suppressed.

[0031] In addition, when the reaction liquid is applied to the liquid film made of the coating liquid applied on the surface of the object to be coated in step 3, the hydrolysis reaction proceeds from the surface of the liquid film toward the inside within several tens of seconds to several minutes, and a glassy coating film is formed. Therefore, when repeating the above-mentioned step 2 and step 3 in this order a required number of times to obtain a desired thickness of the glassy coating film as necessary, it is sufficient to carry out the coating work continuously as it is, and it is not necessary to leave the object to be coated for a predetermined time after carrying out the above-mentioned step 2 and step 3.

[0032] In addition, examples of the application method of the coating liquid and the reaction liquid in the above-mentioned step 2 and the present step 3 include the conventionally known potting method, dip coating method, printing method, spraying method (also referred to as "spray coating method"). Among these, in the invention related to the present application, it is preferable to adopt the spraying method for applying the coating liquid and the reaction liquid in the above-mentioned step 2 and the present step 3. This is because, by performing the application in the above-mentioned step 2 and the present step 3 by the spraying method, it becomes possible to form a glassy coating film on the objects to be coated of various shapes and sizes. In addition, when the application in the above-mentioned step 2 and the present step 3 is performed by the spraying method, there is no particular limitation on the device used to spray the coating liquid and the reaction liquid, respectively, and a conventionally known sprayer such as a commercially available mist sprayer or a spray gun equipped with a two-fluid nozzle may be used.

[0033] When the coating in the above-mentioned step 2 and the present step 3 is performed by a spraying method, the particle size of the droplets when the coating liquid and the reaction liquid are sprayed is preferably 50 μm or less. Here, if the particle size of the droplets when the coating liquid and the reaction liquid are sprayed in the above-mentioned step 2 and the present step 3 exceeds 50 μm, it is undesirable because it tends to result in a non-glossy glass-like coating film. In addition, the particle size of the droplets when the reaction liquid is sprayed in the present step 3 is more preferably 1 μm or less. This is because if the particle size of the droplets when the reaction liquid is sprayed in the present step 3 is 1 μm or less, a glass-like coating film that is more stable, transparent, and has a good appearance tends to be obtained. On the other hand, there is no particular limit to the lower limit of the particle size of the droplets when the coating liquid and the reaction liquid are sprayed in the above-mentioned step 2 and the present step 3, but the particle size of the droplets when the coating liquid and the reaction liquid are sprayed in the above-mentioned step 2 and the present step 3 is preferably 0.1 μm or more. Even if the droplet size of the coating liquid and the reaction liquid sprayed in the above-mentioned step 2 and step 3 is less than 0.1 μm, the film quality of the glassy coating film is not significantly improved, and a relatively expensive sprayer is required to spray the coating liquid and the reaction liquid, which simply tends to increase the production cost.

[0034] When the coating in the above-mentioned step 2 and the present step 3 is performed by a spraying method, the flow velocity of the droplets when the coating liquid is sprayed in the above-mentioned step 2 is preferably 55 m / sec to 145 m / sec, and the flow velocity of the droplets when the reaction liquid is sprayed in the present step 3 is preferably 1 m / sec to 30 m / sec. Here, if the flow velocity of the droplets when the coating liquid is sprayed in the above-mentioned step 2 is less than 55 m / sec, it is not preferable because a part or the whole of the glassy coating film tends to become cloudy. On the other hand, even if the flow velocity of the droplets when the coating liquid is sprayed in the above-mentioned step 2 exceeds 145 m / sec, it is not preferable because the thickness of the glassy coating film obtained in one coating cycle is small, which makes the production more laborious and requires a relatively expensive sprayer to spray the coating liquid, which tends to increase the production cost. In addition, if the flow velocity of the droplets when the reaction liquid is sprayed in step 3 is less than 1 m / sec, the hydrolysis reaction of the components contained in the coating liquid sprayed onto the surface of the object to be coated becomes susceptible to the humidity in the working environment, and a glassy coating film that is transparent and has a good appearance and is reproducible tends not to be obtained, which is undesirable. On the other hand, if the flow velocity of the droplets when the reaction liquid is sprayed in step 3 exceeds 30 m / sec, a glassy coating film having a smooth and substantially uniform thickness does not become obtained, and a part or the whole of the coating tends to become cloudy, which is undesirable.

[0035] Here, in the invention according to the present application, as described above, it is preferable to adjust the amount of the coating liquid and the reaction liquid to be applied on the surface of the object to be coated so that a glassy coating film having a thickness of 0.5 μm to 2.5 μm is formed on the surface of the object to be coated by performing the above-mentioned step 2 and this step 3 in this order once (i.e., performing one application cycle). However, for example, when the object to be coated is a metal material, when the corrosion resistance of the metal material is improved by providing the glassy coating film according to the present application on the surface of the metal material, it is difficult for the glassy coating film of this thickness to fully perform its function. Therefore, it is necessary to further repeat the above-mentioned step 2 and this step 3 in this order until the thickness of the glassy coating film falls within a predetermined numerical range.

[0036] When the corrosion resistance of a metal material is improved by providing the glassy coating film according to the present application on the surface of the metal material, the glassy coating film formed on the surface of the metal material has a suitable thickness of 4.5 μm to 25 μm. If the thickness of the glassy coating film is less than 4.5 μm, the effect of improving the corrosion resistance of the metal material tends not to be obtained, which is not preferable. On the other hand, if the thickness of the glassy coating film exceeds 25 μm, the effect of improving the corrosion resistance of the metal material is not further improved, and defects such as cracks may occur in the glassy coating film, which is not preferable.

[0037] The present invention will be described in more detail below with reference to examples. Note that the present invention should not be construed as being limited to the description of the following examples. EXAMPLES

[0038] In this Example 1, first, 500 ml of methyltriethoxysilane (manufactured by Sigma-Aldrich Japan LLC), 495 ml of vinyltriethoxysilane (manufactured by Sigma-Aldrich Japan LLC), and 5 ml of titanium tetrabutoxide (also known as tetra-n-butyl titanate, manufactured by Kishida Chemical Co., Ltd.) were mixed at 25°C to prepare 1000 ml of a coating liquid (coating liquid consisting only of active ingredients) consisting of 49.75% by mass of methyltriethoxysilane, 49.70% by mass of vinyltriethoxysilane, and 0.55% by mass of titanium tetrabutoxide. Then, 700 ml of pure water (ion-exchanged water) and 300 ml of methyl alcohol were mixed at 25°C to prepare 1000 ml of a reaction liquid consisting of 74.68% by mass of water and 25.32% by mass of methyl alcohol. This Example 1 was carried out indoors at a temperature of 23°C, a relative humidity of 50%, and a pressure of 1 atmosphere (absolute humidity of 10.3 g / m 3 The test and evaluation were carried out under the following conditions:

[0039] Next, two mirror-finished aluminum alloy plates (A5052 aluminum alloy plates) with a thickness of 1 mm, width of 10 cm, and length of 10 cm were prepared, and the surfaces were degreased and cleaned with a commercially available neutral detergent, then rinsed with water and thoroughly dried using an air blow gun. Of these dried aluminum alloy plates, one was covered with a masking tape with a width of 5 mm on one side, and the other was left as it was to be used as a test substrate material. One surface of each of these test substrate materials (the surface on which the masking tape was attached for the test substrate materials partially covered with masking tape) was sprayed with 5.0 ml of the coating liquid prepared above using a commercially available mist spray device equipped with a two-fluid nozzle so as to wet and spread over the entire surface. The fluid sprayed simultaneously with the coating liquid from the two-fluid nozzle was air, the distance between the surface of the aluminum alloy plate and the tip of the spray nozzle of the mist sprayer was 15 cm, the pressure of the mist sprayer during spraying was 0.2 MPa, the aperture diameter of the spray nozzle was 0.3 mm, the average particle size of the droplets near the surface of the aluminum alloy plate determined by the laser diffraction / scattering method was 10 μm, and the flow rate of the mist (droplets) discharged from the mist sprayer was 100 m / sec. According to the change in the mass of the aluminum alloy plate before and after the application of the coating liquid measured with a commercially available electronic balance, the mass of the liquid film made of the coating liquid attached to the surface of the aluminum alloy plate (attached so as to wet and spread over the entire surface of one side of the aluminum alloy plate) was 0.039 g.

[0040] Next, 2.5 ml of the reaction liquid prepared above was sprayed onto each of the two aluminum alloy plates sprayed with the coating liquid, toward the surface side of the plate sprayed with the coating liquid, using a commercially available mist sprayer equipped with the two-fluid nozzle described above, so as to wet and spread over the entire surface of the liquid film made of the coating liquid. The fluid sprayed simultaneously with the reaction liquid from the two-fluid nozzle was air, the distance between the surface of the aluminum alloy plate and the tip of the spray nozzle of the mist sprayer was 30 cm, the pressure of the mist sprayer during spraying was 0.2 MPa, the aperture diameter of the spray nozzle was 0.3 mm, the average particle size of the droplets near the surface of the aluminum alloy plate determined by the laser diffraction / scattering method was 0.8 μm, and the flow velocity of the mist (droplets) discharged from the mist sprayer was 15 m / sec. In addition, according to the change in the mass of the aluminum alloy plate before and after application of the reaction liquid, measured with a commercially available electronic balance, the mass of the reaction liquid attached to the aluminum alloy plate (more precisely, attached so as to spread over the entire surface of the liquid film made of the coating liquid provided on one surface of the aluminum alloy plate) was 0.021 g. Therefore, the mass of water in the reaction liquid attached to the aluminum alloy plate (adhered so as to spread over the entire surface of the liquid film made of the coating liquid provided on one surface of the aluminum alloy plate) relative to the mass of the coating liquid made of the active ingredient attached to the surface of the aluminum alloy plate (adhered so as to spread over the entire surface of the liquid film made of the coating liquid provided on one surface of the aluminum alloy plate) was determined to be 0.40, assuming that the total mass of the active ingredient (i.e., the mass of the coating liquid attached to the surface of the aluminum alloy plate) is 1.

[0041] This "sequential spraying of the coating liquid and the reaction liquid onto the aluminum alloy plate" was counted as one coating cycle, and the coating liquid and reaction liquid were sprayed continuously two more times in the same manner (i.e., a total of three coating cycles were performed), to obtain two test substrate materials (aluminum alloy plates with a glassy coating film) having a transparent, glossy glassy coating film on their surfaces.

[0042] [Evaluation method] Among the aluminum alloy plates with a glassy coating film obtained in Example 1, one sample in which a masking tape had been attached to a part of the surface in advance was peeled off from the surface, and the thickness of the glassy coating film was measured using a contact step gauge, and the thickness was 6.3 μm. Therefore, it can be said that a glassy coating film with an average thickness of 2.1 μm was formed on the surface of the aluminum alloy plate in one application cycle. Next, pure water (ion-exchanged water) was dropped on the surface of this glassy coating film, and the contact angle between the surface of the glassy coating film and the water droplet was measured using a contact angle meter (CA-DT manufactured by Kyowa Interface Science Co., Ltd.). The contact angle was 96 degrees, and the glassy coating film had water repellency. Next, the surface hardness of a part of the glassy coating film was measured based on the scratch hardness (pencil method) of JIS K 5600-5-4, and the surface hardness was equivalent to 3H.

[0043] Furthermore, of the aluminum alloy sheets with a glassy coating film obtained in Example 1, the other sample was sprayed with the coating liquid and the reaction liquid without applying masking tape, and the surface of the aluminum alloy sheet without the glassy coating film was covered with masking tape to prepare a corrosion resistance test sample. This was immersed in a stainless steel square tray in salt water (sodium chloride solution) with a liquid temperature of 25°C and a concentration of 5% by mass and left for 60 hours, then pulled out of the salt water and washed with water, and the appearance was observed, and the surface of the aluminum alloy sheet with the glassy coating film was not corroded. These results are shown in Table 1. EXAMPLES

[0044] This Example 2 differs from Example 1 only in that "spinning of the coating liquid and the reaction liquid on the aluminum alloy plate in succession" was considered as one application cycle, and the coating liquid and the reaction liquid were sprayed in the same manner four more times in succession (i.e., five application cycles in total). Therefore, the description of the test and evaluation methods is omitted. The results of this Example 2 are shown in Table 1. Here, the thickness of the glassy coating film in the aluminum alloy plate with the glassy coating film obtained in Example 2 was 10.4 μm. Therefore, it can be said that a glassy coating film with an average thickness of 2.08 μm was formed on the surface of the aluminum alloy plate in one application cycle. In addition, the contact angle of a water drop on the surface of this glassy coating film was 96 degrees, and the glassy coating film had water repellency. The surface hardness of this glassy coating film was equivalent to 3H. Furthermore, in a corrosion resistance test using salt water, the surface of the aluminum alloy plate provided with the glassy coating film was not corroded. EXAMPLES

[0045] This Example 3 differs from Example 1 only in that "spinning of the coating liquid and the reaction liquid on the aluminum alloy plate in succession" was defined as one application cycle, and the coating liquid and the reaction liquid were sprayed in the same manner nine more times (i.e., ten application cycles in total). Therefore, the description of the test and evaluation methods is omitted. The results of this Example 3 are shown in Table 1. Here, the thickness of the glassy coating film on the aluminum alloy plate with the glassy coating film obtained in Example 3 was 21.1 μm. Therefore, it can be said that a glassy coating film with an average thickness of 2.11 μm was formed on the surface of the aluminum alloy plate in one application cycle. In addition, the contact angle of a water drop on the surface of this glassy coating film was 93 degrees, and the glassy coating film had water repellency. The surface hardness of this glassy coating film was equivalent to 3H. Furthermore, in a corrosion resistance test using salt water, the surface of the aluminum alloy plate provided with the glassy coating film was not corroded. EXAMPLES

[0046] This Example 4 differs from Example 1 only in that the test substrate material was changed from "mirror-finished aluminum alloy plate" to "mirror-finished copper plate (pure copper plate with a thickness of 1 mm, width of 10 cm, and length of 10 cm)". Therefore, the description of the test and evaluation methods is omitted. The results of this Example 4 are shown in Table 1. Here, the thickness of the glassy coating film on the copper plate with a glassy coating film obtained in Example 4 was 6.1 μm. Therefore, it can be said that a glassy coating film with an average thickness of 2.03 μm was formed on the surface of the copper plate in one application cycle. In addition, the contact angle of a water drop with respect to the surface of this glassy coating film was 99 degrees, and the glassy coating film had water repellency. And the surface hardness of this glassy coating film was equivalent to 3H. Furthermore, in a corrosion resistance test using salt water, the surface of the copper material provided with the glassy coating film was not corroded. EXAMPLES

[0047] This Example 5 differs from Example 1 only in that the test substrate material was changed from "mirror-finished aluminum alloy plate" to "anodized aluminum alloy plate (A5052 aluminum alloy plate with a sulfuric acid anodized film having a thickness of 30 μm, the thickness including the anodized film, i.e., the anodized aluminum layer formed by the sulfuric acid method, was 1 mm, the width was 10 cm, and the length was 10 cm)" and that the coating liquid and the reaction liquid were sprayed on the test substrate material only once in succession (i.e., one application cycle was performed). Therefore, the description of the test and evaluation methods is omitted. Note that this Example 5 is mainly intended to provide a water-repellent protective film (coating film) on an anodized aluminum alloy plate, so the "salt water corrosion resistance test" was omitted. In addition, since the surface of the anodized aluminum alloy plate is porous, it is considered difficult to accurately evaluate the film thickness of the glassy coating film, and therefore the "measurement of the film thickness of the glassy coating film" was omitted. The results of this Example 5 are shown in Table 1. The contact angle of a water droplet with the surface of the glassy coating film obtained in Example 5 was 97 degrees, and the glassy coating film had water repellency. The surface hardness of this glassy coating film was equivalent to 3H. EXAMPLES

[0048] This Example 6 differs from Example 1 only in that the test substrate material was changed from "mirror-finished aluminum alloy plate" to "polycarbonate plate (thickness 1 mm, width 10 cm, length 10 cm)" and that the coating liquid and the reaction liquid were sprayed on the test substrate material only once in succession (i.e., one application cycle was performed). Therefore, the description of the test and evaluation methods is omitted. Note that, since this Example 6 is intended to provide a water-repellent protective film (coating film) on a polycarbonate plate, the "salt water corrosion resistance test" was omitted. The results of this Example 6 are shown in Table 1. Here, the thickness of the glassy coating film on the polycarbonate plate with the glassy coating film obtained in Example 6 was 1.9 μm. In addition, the contact angle of a water drop on the surface of the glassy coating film obtained in Example 6 was 95 degrees, and the glassy coating film had water repellency. The surface hardness of this glassy coating film was equivalent to 3H. Comparative Example

[0049] [Comparative Example 1] This Comparative Example 1 differs from Example 1 only in that "a coating liquid consisting of 89.37 mass% methyltriethoxysilane, 10.08 mass% vinyltriethoxysilane and 0.55 mass% titanium tetrabutoxide" was used instead of "a coating liquid consisting of 49.75 mass% methyltriethoxysilane, 49.70 mass% vinyltriethoxysilane and 0.55 mass% titanium tetrabutoxide" and that spraying of the coating liquid and spraying of the reaction liquid were performed on the aluminum alloy plate only once in succession (i.e., one application cycle was performed). Therefore, the description of the test and evaluation methods is omitted. The results of this Comparative Example 1 are shown in Table 1. The coating solution of Comparative Example 1 was obtained by mixing 895 ml of methyltriethoxysilane (Sigma-Aldrich Japan LLC), 100 ml of vinyltriethoxysilane (Sigma-Aldrich Japan LLC), and 5 ml of titanium tetrabutoxide (also known as tetra-n-butyl titanate, Kishida Chemical Co., Ltd.) at 25°C. Here, the thickness of the glassy coating film in the aluminum alloy plate with the glassy coating film obtained in Comparative Example 1 was 1.9 μm. In addition, the contact angle of a water drop with respect to the surface of this glassy coating film was 76 degrees, and the glassy coating film did not have water repellency. The surface hardness of this glassy coating film was equivalent to 3H. Furthermore, in a corrosion resistance test using salt water, the surface of the aluminum material provided with the glassy coating film was partially corroded, and the corrosion resistance was insufficient.

[0050] [Table 1] [Industrial Applicability]

[0051] The invention of the present application can be used when forming a glassy coating film on the surface of a product made of a metal or resin material, such as daily necessities, automobile bodies and parts, aircraft bodies and parts, etc. In particular, the invention can be suitably used as a technology for forming a glassy coating film on the surface of a product made of a metal or resin material used outdoors, such as an automobile body and parts, an aircraft body and parts, to protect the surface of the product from various external factors such as ultraviolet rays and dust, and to impart high water repellency and corrosion resistance.

Claims

1. A method for forming a glassy coating film on an object to be coated in order to impart water repellency to the object, the method comprising the following steps 1 to 3: Step 1: The surface of the object to be coated, which is made of a metal or resin material, is degreased, cleaned, and then dried. Step 2: Absolute humidity 18.4 g / m 3 Under the following conditions, a coating liquid containing 80% by mass or more of active ingredients consisting of 15% by mass to 65% by mass of vinyltrimethoxysilane or vinyltriethoxysilane, 0.3% by mass to 2.7% by mass of titanium tetrabutoxide, and the remainder being methyltrimethoxysilane or methyltriethoxysilane, is applied to the surface of the object to be coated after drying. Step 3: Absolute humidity 18.4 g / m 3 Under the following conditions, a reaction liquid containing 65% or more by mass of water is applied to the object to be coated to which the coating liquid has been applied, to form a glassy coating film on the surface of the object to be coated.

2. 2. The method for forming a glassy coating film according to claim 1, wherein the temperature of the coating liquid in step 2 and the reaction liquid in step 3 is 5° C. to 55° C.

3. 3. The method for forming a glassy coating film according to claim 1, wherein when the coating in step 2 and step 3 is performed by a spraying method, the particle size of droplets when the coating liquid and the reaction liquid are sprayed is 50 μm or less.

4. 3. The method for forming a glassy coating film according to claim 1 or 2, wherein, when the coating in step 2 and step 3 are performed by a spraying method, a flow velocity of droplets when the coating liquid is sprayed in step 2 is 55 m / sec to 145 m / sec, and a flow velocity of droplets when the reaction liquid is sprayed in step 3 is 1 m / sec to 30 m / sec.

Citation Information

Patent Citations

  • Corrosion-resistant water-based coating composition and corrosion-resistant coated aluminum material

    JP2007169353A

  • Method for formation of coating film and coating fluid

    JP2010155727A